2021
DOI: 10.1002/adma.202107512
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Stable 2D Cr5Te8 Nanosheets with Thickness‐Tunable Ferromagnetism

Abstract: Abstract2D magnetic materials have aroused widespread research interest owing to their promising application in spintronic devices. However, exploring new kinds of 2D magnetic materials with better stability and realizing their batch synthesis remain challenging. Herein, the synthesis of air‐stable 2D Cr5Te8 ultrathin crystals with tunable thickness via tube‐in‐tube chemical vapor deposition (CVD) growth technology is reported. The importance of tube‐in‐tube CVD growth, which can significantly suppress the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
103
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 47 publications
8
103
0
1
Order By: Relevance
“…The lattice spacing of the diffraction spots marked by yellow circles is 2.88 Å, which is consistent with the measured (100) lattice spacing of monolayer WSe2. The diffraction spots marked with red circles show identical orientation with that of the WSe2, with a lattice spacing of 3.36 Å in accordance with the Cr5Te8 (200) planes, which reduces by ~2% from the value of freestanding Cr5Te8 [20] . The inner, red-circled diffraction spots with a larger periodicity (6.72 Å) representing those ordered, self-intercalated Cr atoms An atomic model of the Cr5Te8/WSe2 heterostructure based on iterative refinements from HAADF-STEM image analysis and first principles calculations is shown in Figure 2e, where a 3 × 3 Cr5Te8 supercell is commensurate with the 7 × 7 WSe2 supercell.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The lattice spacing of the diffraction spots marked by yellow circles is 2.88 Å, which is consistent with the measured (100) lattice spacing of monolayer WSe2. The diffraction spots marked with red circles show identical orientation with that of the WSe2, with a lattice spacing of 3.36 Å in accordance with the Cr5Te8 (200) planes, which reduces by ~2% from the value of freestanding Cr5Te8 [20] . The inner, red-circled diffraction spots with a larger periodicity (6.72 Å) representing those ordered, self-intercalated Cr atoms An atomic model of the Cr5Te8/WSe2 heterostructure based on iterative refinements from HAADF-STEM image analysis and first principles calculations is shown in Figure 2e, where a 3 × 3 Cr5Te8 supercell is commensurate with the 7 × 7 WSe2 supercell.…”
Section: Resultsmentioning
confidence: 89%
“…The diffraction spots marked with red circles show identical orientation with that of the WSe 2 , with a lattice spacing of 3.36 Å in accordance with the Cr 5 Te 8 (200) planes, which reduces by ≈2% from the value of freestanding Cr 5 Te 8 . [20] The inner, redcircled diffrac tion spots with a larger periodicity (6.72 Å) representing those ordered, selfintercalated Cr atoms is a structural fingerprint of trigonal Cr 5 Te 8 . Interestingly, the innermost diffraction spots highlighted by blue circles indicate a lattice spacing of 11.6 Å, which belongs to neither WSe 2 nor Cr 5 Te 8 alone, of interfacial Cr atoms to be reduced to 3 per supercell from 9 selfintercalated in the interior of Cr 5 Te 8 , suggesting inter facial reconstruction.…”
Section: Resultsmentioning
confidence: 98%
“…[1][2][4][5][6][7][8][9][10] Based on first-principles calculations, hundreds of 2D vdW magnets have been predicted for breakthroughs to realize controlled synthesis of 1 and 2 unit-cell CrSe and Cr 2 Te 3 by CVD growth and found these 2D ultrathin films show obvious thickness-dependent Curie temperature, the highest value is 280 K. Xu et al [36] reported that hexagonal CrTe 2 monolayer grown on bilayer graphene substrates by MBE with T C = 200 K. Zhang et al [37] reported that trigonal ultrathin Cr 2 Te 3 films are FM with T C = 195 K and exhibit strong perpendicular magnetic anisotropy with 5 × 10 6 J m −3 , and Li et al [38] prepared 2D nanosheets of α-MnSe 2 with nonstoichiometric surfaces via soft chemical etching, which were found to be a FM semiconductor with T C = 320 K. In addition, the robust FM/AFM order have also been found in 2D non-vdW CrSe 2 , Fe 7 Se 8 , Cr 5 Te 8 , FeTe, CrTe, α-MnSe 2 , and FeSe ultrathin films, their T C is up to 110, 300, 160, 220, 367, 160, and 553 K, respectively. [27,28,31,[38][39][40][41] Compared to 2D vdW magnets, 2D non-vdW ultrathin films have strong interlayer chemical bonding. Intuitively, the Curie temperature in the 2D non-vdW magnetic materials could be significantly elevated by the enhanced interlayer magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[39] The CVD-grown 2D Cr 5 Te 8 is an air-stable FM material, the signal of magnetooptical Kerr effect is well maintained after aging in air for 3 months. [28] As shown in the X-ray diffraction pattern and M-H hysteresis measurement, the structures of 2D CrTe ultrathin crystals are stable even after 1-month exposure in ambient air and their strong intrinsic ferromagnetism still remained. [22] Moreover, the 2D hexagonal AFM semiconductor FeSe with few unit-cell thicknesses are also quite stable, and it could remain without phase transformation after exposure to air for a month or being heat treated at 600 K for 1 h under a N 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation